Odpowiedź:
1.
P = (6 , - 5 ) , Q = ( - 1 , - 5 )
xp = 6 , xq = - 1 , yp = - 5 , yq = - 5
(xq - xp)(y - yp) = (yq - yp)(x - xp)
(- 1 - 6)(y + 5)= (- 5 + 5)(x - 6)
- 7(y + 5) = 0 * (x -6)
- 7y - 35 = 0
- 7y = 35
7y = - 35
y = - 35/7 = - 5 funkcja liniowa stała
2.
P = (- 7, 8 ) , Q = ( - 7 , 0 )
xp = - 7 , xq = - 7 , yp = 8 , yq = 0
(xq - xp)(y - yp) = (yq - yp)(x - xp)
(- 7 + 7)(y - 8) = (0 - 8)(x + 7)
0 * (y - 8) = - 8(x +7)
- 8x - 56 = 0
- 8x = 56
8x = - 56
x = - 56/8 = - 7 funkcja liniowa stała